The Influence Of Organizational Culture, Work Ethic, And Work Communication On Employee Productivity At The Commission For The Prosecution Of The Republic Of Indonesia - Syafrinaldi Syafrinaldi; Cut Zurnali (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the influence of organizational culture, work ethic, and work communication on employee productivity at the Commission for the Prosecution of the Republic of Indonesia (KKRI). Employing a quantitative research approach, data were collected from 40 employees through a structured questionnaire and analyzed using multiple linear regression. The results reveal that organizational culture, work ethic, and communication each have a positive and significant effect on employee productivity. Organizational culture and communication demonstrate a strong influence, while work ethic shows a moderate yet meaningful impact. Furthermore, the simultaneous analysis confirms that the three variables together significantly contribute to explaining variations in productivity. These findings suggest that strengthening organizational culture, fostering a robust work ethic, and enhancing effective communication are critical strategies to improve productivity within public institutions. Future research is recommended to explore moderating or mediating variables to further enrich the understanding of these relationships in various organizational contexts.